Determinan Minat Penggunaan Sistem Pembayaran Non Tunai Berbasis Qris Oleh UMKM di Kecamatan Dompu - Qoriatun, Istiana; Chaidir, Taufiq; Yudha , I Dewa Ketut (Green Publisher Indonesia, 2025)
This studyaims to analyze the influence of perceived ease, perceived usefulness, financial literacy, and motivation on the interest of MSMEs in using QRIS.Data was collected through a questionnaire survey of SME operators in Dompu Subdistrict.This study employs a quantitative approach using the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS). The resultsof the study indicate that motivation has a positive and significant influence on the interest in using QRIS. Meanwhile, perceived ease, perceived benefit, and financial literacy did not show a significant influence on interest in using QRIS. These findings indicate that the motivation factor plays a key role in driving QRIS adoption among SMEs in the study area, while the other factors tested did not have a significant impact.